PENTINGNYA RATIFIKASI MADRID PROTOCOL DALAM MENGHADAPI PERDAGANGAN BEBAS DI ERA GLOBALISASI - Trias Palupi Kurnianingrum (Pusat Penelitian Politik, 2010)
Nowadays Indonesia and other developing countries can not be avoided and have toface the era of globalization and trade liberalization which include free competition of the economy and the utilization of intellectual property In thefield of the protection ofintellectualproperty rights similarity ofgoods and services traded across borders requires the existence of the concept ofequal protection oflaw standards which underlies the importance of ratification ofMadrid Protocolfor Indonesia especially forfacing the challenges offree trade area today since the protection of trademarks are needed particularly for maintaining the fair competition and also prevent plagiarism